Pigmented flower extracts of plant species from the Geraniaceae and Lamiaceae families as natural food colourants: anthocyanin composition, thermal and oxidative stability. (29th April 2022) - Venter, Anton; Fisher, Hennie; Stafford, Gary I.; Duodu, Kwaku Gyebi
Summary: This study determined the anthocyanin profile of pigmented flower extracts from some Geraniaceae and Lamiaceae plant species found in South Africa, and their thermal and oxidative stability to assess their potential food application. Anthocyanins in the Geraniaceae ( Pelargonium grandiflorum Willd. and Pelargonium × hortorum L.H. Bailey, Pelargonium zonale hybrid) were 3, 5‐diglucosides of delphinidin, petunidin, pelargonidin, peonidin and malvidin and acetyl‐acylated malvidin, delphinidin and petunidin. The Lamiaceae species ( Salvia aurea × dolomitica Bae's blue, Salvia dolomitica Codd and Plectranthus zuluensis T. Cooke) mainly contained rutinosides of pelargonidin, glucosides of petunidin, pelargonidin and p ‐coumaric acid‐ and malonyl‐acylated delphinidin and malvidin. Lamiaceae pigments had higher thermal and oxidative stability. This could be due to aromatic malonyl‐acylated anthocyanin self‐association and strong intermolecular interactions with phenolic acids and derivatives. Flowers from Lamiaceae and Geraniaceae have potential application as natural food colourants, but temperature and oxidising conditions must be considered depending on the particular species being used. Abstract : Pigmented flower extracts from the Geraniaceae plant family contain acetyl acylated anthocyanins while extracts from the Lamiaceae plant family contain aromatic‐malonyl acylated anthocyanins. Pigmented extracts from the Lamiaceae family are more thermally and oxidatively stable than pigments from the Geraniaceae family. Rosmarinic acid and derivatives in Lamiaceae pigments could interact with anthocyanins and confer stability.